Effects of ginseng on the proliferation of human lung fibroblasts - Yoo, HH; Yokozawa, T; Satoh, A; Kang, KS; Kim, HY (WORLD SCIENTIFIC PUBL CO PTE LTD, 2006)
In this study, we investigated the effects of methanolic extracts of white ginseng (Panax ginseng C.A. MEYER) and two kinds of heat-treated ginseng made by steaming fresh ginseng at 100 degrees C for 3 hours (HTG-100) or 120 degrees C for 3 hours (HTG-120) on the cell growth of human fibroblasts. All of the tested ginseng extracts stimulated cell growth, although the effect of HTG-120 was weaker than that of the other extracts. However, none of the ginseng extracts exhibited any effect on the growth of old cells with a population doubling level (PDL) of 48.7. Flow cytometric analysis showed that ginseng extracts raised the population of cells in G(0)/G(1) phase after treatment for 24 hours, but did not exert any effect after treatment for 48 hours. These results suggest that ginsengs exert their cell growth-promoting action mainly on younger cells at an early stage of the cell cycle, and that this effect is closely associated with an increase in the population of cells in the G(0)/G(1) phase.
Keywords: PANAX-GINSENG; REPLICATIVE SENESCENCE; SK-HEP-1 CELLS; MELANOMA-CELLS; RED GINSENG; CANCER; GINSENOSIDES; GROWTH